Quality of Nursing Work Life and Nurses' Behaviour in Documenting Integrated Patient Progress Notes in Hospital - Ade Faiz Ahmadi; Dwi Prasetyaningati; Anita Rahmawati; Daviq Ayatulloh; Diah Priyantini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: The quality of nurses' work life pays attention to the fulfillment of nurses' needs which will have an influence on nursing services and organizational productivity. The purpose of the study was to analyze the relationship between quality of nursing work life (QNWL) and nurse behavior in documenting integrated patient progress notes. Methods: This study is quantitative in nature with a cross-sectional approach and took a population of 40 nurses in abimanyu room of jombang hospital. This sampling technique uses total sampling. The independent variable in this study was QNWL, using the QNWL questionnaire instrument, while the dependent variable was nurse behavior in documenting patient development records, using a nurse behavior questionnaire instrument modified by the researcher and declared valid (calculated r = 0.904) and reliable (Cronbach alpha = 0.961) and tested using SPSS version 16.0 with the Spearman's rho statistical test. Results: The best QNWL indicator was Work life-Home life, with 34 respondents (85.0%). Meanwhile, knowledge, which is an indicator of nurses' behavior in CPPT documentation, showed the highest score with 35 respondents (87.5%), thus forming behavior in the positive category. Based on the results of the the Spearman's rho statistical test with the SPSS program, dengan nilai r = 0.476 and with significant value P = 0.002 Conclusions: This study concluded that QNWL among nurses at a hospital in Jombang was almost entirely in the good category, with nurses exhibiting positive behavior in documenting integrated patient progress notes